2008
DOI: 10.1523/jneurosci.2565-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Altered Molecular Regionalization and Normal Thalamocortical Connections in Cortex-SpecificPax6Knock-Out Mice

Abstract: Transcription factor Pax6 exerts a prominent rostrolateral high to caudomedial low expression gradient in the cortical progenitors and have been implicated in regulation of area identity in the mammalian cortex. Herein, we analyzed the role of Pax6 in molecular arealization and development of thalamocortical connections in the juvenile cortex-specific conditional Pax6 knock-out mice (Pax6cKO). Using a set of molecular markers of positional identity (Id2, Cadherin6, COUP-TF1, RZR␤, and EphA7), we show that, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 52 publications
8
53
0
Order By: Relevance
“…In this line of evidence, previous data indicated that overexpression of Pax6 in vivo affected the RG proliferation and caused progenitor apoptosis only during early neurogenesis (Berger et al, 2007). Notably, the expansion of IGLs and the reduction of SGL neuronal sets observed in Emx1-Cre/Pax6cKO mice was predominant in the rostral cortex, which correlates with a severe diminishing of the motor area size in these mutants (Piñon et al, 2008). We propose, therefore, that Pax6 deficiency, with failure in progenitor cell cycle progression at the onset of cortical neurogenesis, causes both laminar and area disturbances of the mature rostral cortex.…”
Section: Pax6 Controls Distinct Neural Subprograms During Corticogenesissupporting
confidence: 53%
See 3 more Smart Citations
“…In this line of evidence, previous data indicated that overexpression of Pax6 in vivo affected the RG proliferation and caused progenitor apoptosis only during early neurogenesis (Berger et al, 2007). Notably, the expansion of IGLs and the reduction of SGL neuronal sets observed in Emx1-Cre/Pax6cKO mice was predominant in the rostral cortex, which correlates with a severe diminishing of the motor area size in these mutants (Piñon et al, 2008). We propose, therefore, that Pax6 deficiency, with failure in progenitor cell cycle progression at the onset of cortical neurogenesis, causes both laminar and area disturbances of the mature rostral cortex.…”
Section: Pax6 Controls Distinct Neural Subprograms During Corticogenesissupporting
confidence: 53%
“…Defects in differentiation of late-prenatal and postnatal RG progenitors in Emx1-Cre/Pax6cKO mutant The brain of the juvenile (P10) Emx1-Cre/Pax6cKO mouse contains dense cell masses at the PSPB (Piñon et al, 2008). These large cell protrusions were strongly labeled by the subpallial markers, Dlx1 (Fig.…”
Section: Absence Of Pax6 Causes Sgl Dysgenesis But Does Not Affect Thmentioning
confidence: 97%
See 2 more Smart Citations
“…Of these transcription factors, evidence supports a patterning role for Sp8 and Emx2, whereas the effects of Pax6 on area patterning have been recently suggested by both gain-and lossof-function studies to be indirect (Fig. 3B) (Manuel et al 2007;Pinon et al 2008).…”
Section: Gradients Of Transcription Factors Refine Area Patterningmentioning
confidence: 92%